Immunofocusing using conformationally constrained V3 peptide immunogens improves HIV-1 neutralization. Issue 2 (5th January 2017) - Moseri, Adi; Sinha, Eshu; Zommer, Henni; Arshava, Boris; Naider, Fred; Anglister, Jacob
Highlights: Sequential immunization with long and short constrained V3-peptide immunogens is described. 18–19 residue loop priming peptides followed by 10–14 residue loop focusing peptides were used. The protocol was designed to focus the immune response on the V3 tip of HIV-1 gp120. The immunofocusing protocol resulted in an increased percentage of Abs recognizing the V3 tip. The sequential approach was superior to repeated immunization with the same peptide. Abstract: V3-directed antibodies are present in practically all HIV-1 infected patients and in individuals vaccinated with gp120. The levels of maternal V3-directed antibodies were recently shown to correlate with reduced mother to child transmission, and V3 IgGs were found to be a negative correlate of risk in the RV-144 human trial. mAb directed to the tip of the V3 are capable of broad neutralization of Tier-1 and some Tier-2 viruses. Here we report an immunofocusing approach using conformationally constrained V3 peptides of different lengths. Immunofocusing with short constrained V3 peptides following immunizations with long constrained V3 peptides resulted in sera with improved neutralization of Tier-1B viruses in comparison with immunizations with the long constrained peptide alone. Immunizations only with the short constrained peptide were ineffective. Our results demonstrate that immunofocusing with constrained V3 peptides of different lengths could improve the induction of HIV-1 neutralizing antibodies.